2013
DOI: 10.1021/ja3106797
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Photo-oxidation of Methanol to Methyl Formate on TiO2(110)

Abstract: Methyl formate is produced from the photo-oxidation of methanol on preoxidized TiO(2)(110). We demonstrate that two consecutive photo-oxidation steps lead to methyl formate using mass spectrometry and scanning tunneling microscopy. The first step in methanol oxidation is formation of methoxy by the thermal dissociation of the O-H bond to yield adsorbed CH(3)O and water. Formaldehyde is produced via hole-mediated oxidation of adsorbed methoxy in the first photochemical step. Next, transient HCO is made photoche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
245
3
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(271 citation statements)
references
References 17 publications
19
245
3
4
Order By: Relevance
“…In a recent study employing temperature programmed desorption (TPD) and scanning tunneling microscopy (STM), Friend and co-workers have deduced the mechanism of CH 3 OH photooxidation on a preoxidized TiO 2 (110) surface. 23 They concluded that coadsorbed oxygen atoms first reacted thermally with CH 3 OH to produce adsorbed CH 3 O and H 2 O. Then CH 3 O underwent photo-oxidation to HCOOCH 3 in a two-step process where the CH 3 O dissociated to CH 2 O and a crosscoupling reaction involving an HCO intermediate led to the formation of HCOOCH 3 .…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study employing temperature programmed desorption (TPD) and scanning tunneling microscopy (STM), Friend and co-workers have deduced the mechanism of CH 3 OH photooxidation on a preoxidized TiO 2 (110) surface. 23 They concluded that coadsorbed oxygen atoms first reacted thermally with CH 3 OH to produce adsorbed CH 3 O and H 2 O. Then CH 3 O underwent photo-oxidation to HCOOCH 3 in a two-step process where the CH 3 O dissociated to CH 2 O and a crosscoupling reaction involving an HCO intermediate led to the formation of HCOOCH 3 .…”
Section: Introductionmentioning
confidence: 99%
“…17,18 In other studies, molecular methanol was considered to undergo photoinduced dissociation to methoxy through the breaking of the O-H bond, 18,21,33 and then further photooxidized into formaldehyde and methyl formate. 22,23,33,34 Thus, a stepwise breaking of C-H bond, or stepwise photooxidation of methoxy was suggested. However, methoxy was identified to be a photoactive species while the molecularly adsorbed methanol was considered to be photoinactive.…”
mentioning
confidence: 99%
“…The highest yield of methyl formate was measured for Pt/TiO 2 (62.2) and the lowest one for Ru/TiO 2 (26.0). Recent studies performed under UHV conditions on preoxidized TiO 2 (110) disclosed that methyl formate is produced from the photo-oxidation of methanol even at ~200 K [41]. The finding that methyl formate is produced in the photocatalytic decomposition of DME further supports the idea that CH 3 O species is involved in its photoreaction The formation of methyl formate can be ascribed to the recombination of CH 2 O formed in the dissociation of CH 3 O (Equation (3)):…”
Section: Catalytic Studiesmentioning
confidence: 83%